O estádio do espelho em Lacan e a dialética do reconhecimento - César, Lara Mendes (2020)
The present dissertation is the result of a theoretical and bibliographic research that aimed to investigate the resonances of the dialectic of recognition in the text The mirror stadium as a form of the function of the self - as revealed to us by the psychoanalytic experience (1949), by Jacques Lacan. Once the psychoanalyst introduced himself to the Hegelian dialectic at the hands of the Russian philosopher Alexandre Kojève, the analysis makes the comparison between the four fundamental premises of the dialectic of recognition, in his Kojèvian interpretation (the existence of the revelation of the Being through the word; the existence of a desire that generates a negative action of the given Being; the existence of a multiplicity of desires, capable of desiring each other; and the possibility of a difference between the desires that make up the relationship of domination and servitude) and the crucial analytical categories of the Lacanian elaborations , in the writings published between 1936 and 1949, about the constitution of the subject and the formation of the self (identification, narcissism, paranoid knowledge, aggressiveness, secondary identifications and function of the [self]). Finally, considerations are made regarding the negative ontological structure that Kojève deals with in his reading of the dialectic of recognition and which underlies Lacan's theorization in The Mirror Stadium (The Looking-Glass phase).